Benin : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
This paper reviews Benin's Poverty Reduction Strategy Paper (PRSP) for 2003-05. Benin's PRSP represents, on the one hand, an overall strategy for combating poverty which, instead of focusing solely on economic growth or exclusively on social services, integrates all the dimensions of development and poverty reduction. On the other hand, this strategy, without neglecting to take poverty in urban or adjacent areas into account, places greater emphasis on rural development. Moreover, the PRSP has been prepared with the participation of the targeted population groups.